Adherence and its impact on the reduction of lipid peril of patients seen in the form of telemedicine at a state university in Costa Rica (UNED Research Journal, 2015)
Cardiovascular disease is the leading cause of morbidity and mortality worldwide. Costa Rica is no exception, with high levels of cholesterol and triglycerides in all age groups, and lack of adherence to treatment as one of the main challenges. We analyze the variation in test results of lipid pro le in one control and one telemedicine group in the staff of a Costa Rican university. We followed 62 patients aged 20-70 years, with tests done after fasting 12 hours, and 6 months to a year between samples. A questionnaire was used to calculate rates of factors that affect the variation in laboratory results. The patients had greater commitment to self care in the telemedicine group, achieving a reduction in total cholesterol levels, with little or no variation in other lipoproteins, and a slight increase in triglyceride levels.
Keywords: Telemedicine; dyslipidemia; cardiovascular risk; lipid disorders; treatment adherence; lifestyle.